ROLE OF DIFFERENT MEDIUM ON ABHRAKA SHODHANA A PHARMACEUTICAL STUDY - Pankaj Rai; Laxmi Narayan Gupta; Siddaram Arawatti; Neeraj Kumar (International Journal of Applied Ayurved Research, 2015)
Metals and minerals are used in Ayurveda in the form of bhasma to treat patients since thou-sands of year. Bhasma, is a ayurvedic metallic/mineral preparation treated with herbal juices or decoction and exposed for certain quantum of heat as per puta system described in marana (calcination). Before the process of marana, shodhana (purification) process is carried out. Abhraka is an important mineral of much therapeutic purposes. Many liquid medium are mentioned in Ayurvedic texts for Abhraka shodhana. In this paper an attempt is made to find out the role of different medium in the pharmaceutical process of Abhraka.